Therapeutic effects and mechanism analysis of Paeonia lactiflora extract (PLE) in menopausal rats with hot flashes - Cui, Weilin; Song, Tingting; Gao, Dongmei; Wang, Xiaoyu; Sun, Ya; Fu, Liyu; Han, Yichao; Wang, Jieqiong (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceMenopausal syndrome (MPS) is a symptom of physical and psychosomatic abnormalities that women may face around the time of menopause. Hot flashes are the main symptom. Paeonia lactiflora extract (PLE) is the active ingredient extracted from Radix Paeonia alba. It can be used to treat MPS, such as hot flashes. However, its pharmacologic mechanism is unclear.Aim of the studyThis study aims to comprehensively evaluate the effect of PLE on menopausal hot flashes, and to analyze the mechanism of action of PLE in the treatment of menopausal hot flashes from the perspective of neural pathways, to provide a research strategy and experimental basis for the study of similar new drugs and the pathogenesis of MPS.Materials and methodsFirst, we screened menopausal rats through the natural aging model. After 14 days of therapeutic drug gavage, a menopausal hot flashes model was induced in menopausal rats by gavage with thyroid tablet suspension (160 mg/kg) for 14 days. The changes in facial and tail temperature of rats in each group were observed; the behavioral characteristics of rats in each group were followed by an open field test, elevated plus maze and aggressive behavior test; the contents of estradiol, luteinizing hormone, follicle stimulating hormone, 5-hydroxytryptamine, cyclic guanosine monophosphate and cyclic adenosine monophosphate were detected by ELISA; the pathological changes of the uterus were detected by HE staining method. Combined with transcriptomics technology, high-throughput transcriptome sequencing was performed on the hypothalamus of control, model and PLE (160 mg/kg) group, and differential gene analysis between control and model groups, and PLE (160 mg/kg) group and model group was performed using DESeq2. qRT-PCR and Western blot were used to further validate the candidate core genes.ResultsPLE improved the mental status of model rats and reduced the abnormal tail temperature elevation in model rats. In addition, PLE had the effect of increasing the estradiol content and decreasing the luteinizing hormone content in the serum of rats, and the administration of 160 mg/kg of PLE also significantly increased the 5-hydroxytryptamine content in the serum of rats. In terms of pathological manifestations, the model rats had significantly thinner endometrial thickness, looser tissues and reduced integrity, while the rats intervened by PLE treatment had significantly thicker endometrium and more regularly arranged tissue structure. Therefore, it can be determined that PLE has a good pharmacological basis for the treatment of menopausal hot flashes. The transcriptomic analysis showed that 210 genes were significantly altered in the control and drug administration groups together, and the candidate core genes related to neuroendocrine were screened out based on the comprehensive literature and previous studies, and it was further found that PLE may achieve ASIC4, cplx1, mRNA expression levels, and Tac3, Tacr3 protein expression levels by up-regulating neuroprotective effects, thereby restoring the normal neuroendocrine environment of menopausal hot flashes in rats.ConclusionPLE can effectively alleviate thyroid tablet-induced menopausal hot flashes, and the mechanism may be related to the regulation of abnormal expression of ASIC4, cplx1, GnRH1, Tac3, and Tacr3 in the hypothalamus, thereby restoring the imbalanced hypothalamic-pituitary-gonadal axis.